2017
DOI: 10.1155/2017/3974291
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenoma and Hyperprolactinemia Accompanied by Idiopathic Granulomatous Mastitis

Abstract: Idiopathic granulomatous mastitis (IGM) is a rare chronic inflammatory disease of the breast, and its etiology remains not fully elucidated. IGM is observed more often in patients with autoimmune disease. Hyperprolactinemia is observed during pregnancy, lactation, and a history of oral contraceptive use. A 39-year-old patient with no history of oral contraceptive use presented with complaints such as redness, pain, and swelling in her left breast. Ultrasound and magnetic resonance imaging (MRI) revealed a susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…GLM patients are generally women of childbearing age, especially those who use oral contraceptive or have a history of breastfeeding, and secondary GLM in patients with pituitary adenomas has been reported (Destek et al, 2017, Goldberg et al, 2000, Laghzaoui Boukaidi et al, 2000, Uysal et al, 2018. Therefore, the abnormal increase of sex hormone level may also be one of the important causes of GLM.…”
Section: Discussionmentioning
confidence: 99%
“…GLM patients are generally women of childbearing age, especially those who use oral contraceptive or have a history of breastfeeding, and secondary GLM in patients with pituitary adenomas has been reported (Destek et al, 2017, Goldberg et al, 2000, Laghzaoui Boukaidi et al, 2000, Uysal et al, 2018. Therefore, the abnormal increase of sex hormone level may also be one of the important causes of GLM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 28 ] The above causes result in elevated inflammatory cytokines, leaving the body in a state of inflammatory stress, and ultimately causing the pathogenesis of inflammatory diseases. [ 3 , 24 ] This study showed that patients with GLMs had higher levels of WBC, PLT, CRP, IL-2, and TGF-β compared with non-GLM controls, showing the increased inflammatory stress in GLM patients compared with non-GLM controls. Although the levels of these parameters were within a normal range in most GLM patients, the higher levels of them in GLM patients indicated that they were in a state of imbalanced immune function and inflammatory stress.…”
Section: Discussionmentioning
confidence: 76%
“…They also reported that five patients taking antipsychotic medications developed PDM, while psychotropic-associated PDM had not yet been reported. Destek et al [9]. reported that a patient diagnosed with idiopathic granulomatous mastitis initially presented with pituitary prolactinoma.…”
Section: Discussionmentioning
confidence: 99%